Factors influencing quality of life of patients after the acute pancreatitis - Chmiel, Izabela (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Acute pancreatitis (AP) is a significant challenge for the modern medicine for medical reasons, social and economic aspects. Patients with acute pancreatitis demonstrate physical, psychological and social problems. Aim. The aim of the study was to assess the quality of life of convalescents after moving pancreatitis, hospitalized from 2000 to 2006 in the Jagiellonian University in Cracov. Material and methods. The study involved 142 adults — 61 women and 81 men, aged from 22 to 69 years. Three investigational methods were used: a retrospective analysis of medical records, original questionnaire and standardised questionnaire SF-36. Results and conclusions. Demographic and social parameters, such as gender, education, occupational status, are the principal factors influencing individual components of quality of life evaluated with the SF-36 questionnaire. However, clinical variables related to acute pancreatitis, i.e. severity of disease, therapy, and complications have a limited impact on patients quality of life. Results of the study demonstrated that parameters related to quality of life obtained in the study population with the SF 36 questionnaire were markedly lower, but not significantly different, from normal results for the general US population or patients surviving acute pancreatitis in Finland. The results may be helpful in estimating the scope of the social needs of the traveling disease in the education of medical professionals, as well as directly in the planning of rehabilitation. Nursing Topics 2014; 22 (4): 426–432